2020
DOI: 10.2174/1385272824666200120144305
|View full text |Cite
|
Sign up to set email alerts
|

Green Chemistry Approaches to the Synthesis of Coumarin Derivatives

Abstract: This review is a compilation of the green synthetic methods used in the synthesis of coumarin derivatives. Coumarins are a class of compounds with a pronounced wide range of biological activities, which have found their application in medicine, pharmacology, cosmetics and food industry. Their biological activity and potential application are highly dependent on their structure. Therefore, many researchers have been performing the synthesis of coumarin derivatives on a daily basis. High demands for their synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 120 publications
0
25
0
Order By: Relevance
“…Due to the length of this general overview, synthetic strategies for obtaining new coumarins have not been discussed in detail. To find information on the most recent synthetic pathways, we recommend the manuscripts by Molnar and co-authors [ 81 ] and Kovač and co-authors [ 82 ], both from 2020. To find an overview of the wide range of biological activities of coumarins, a 2020 review by Pinto and co-authors [ 1 ] is strongly recommended.…”
Section: Perspectivesmentioning
confidence: 99%
“…Due to the length of this general overview, synthetic strategies for obtaining new coumarins have not been discussed in detail. To find information on the most recent synthetic pathways, we recommend the manuscripts by Molnar and co-authors [ 81 ] and Kovač and co-authors [ 82 ], both from 2020. To find an overview of the wide range of biological activities of coumarins, a 2020 review by Pinto and co-authors [ 1 ] is strongly recommended.…”
Section: Perspectivesmentioning
confidence: 99%
“…Alizadeh et al reported a sequential three-component reaction of salicylaldehydes 60 , β-keto esters 61, and p -toluenesulfonylmethyl isocyanide (TosMIC) ( 62 ) via [ 1 , 3 ] acyl shift to give 2-acyl[1] benzopyrano[3,4- e ]pyrrol-4-ones 63 ( Scheme 18 ) [ 67 ]. A simple workup procedure, mild reaction conditions, lack of side products, and good yields of 62%–95% are the main aspects of this method.…”
Section: Synthesis Of Benzopyrone-fused Five-membered Aromatic Hementioning
confidence: 99%
“…Coumarins are a family of benzopyrones (1,2-benzopyrones or 2 H -[1]benzopyran-2-ones), which represent an important family of oxygen-containing heterocycles, widely distributed in nature [ 1 , 2 , 3 , 4 ]. Coumarins display a broad range of biological and pharmacological activities, [ 5 , 6 ] such as antiviral [ 7 , 8 , 9 , 10 ], anticancer [ 11 , 12 , 13 ], antimicrobial [ 14 , 15 ], and antioxidant [ 16 , 17 , 18 ] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Coumarin is one of the benzopyrones (1,2-benzopyrones or 2H-[1] benzopyran-2-ones) and represents an important family of oxygen-containing heterocycles widely distributed in nature [ 1 ]. The incorporation of another heterocyclic moiety into coumarin enriches the properties of the parent structure and the resulting compounds may exhibit promising properties [ 2 , 3 , 4 , 5 ]. Certain derivatives of 3,4-heterocycle-fused coumarins play an important role in medicinal chemistry and have been extensively used as versatile building blocks in organic synthesis [ 2 , 3 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of another heterocyclic moiety into coumarin enriches the properties of the parent structure and the resulting compounds may exhibit promising properties [ 2 , 3 , 4 , 5 ]. Certain derivatives of 3,4-heterocycle-fused coumarins play an important role in medicinal chemistry and have been extensively used as versatile building blocks in organic synthesis [ 2 , 3 , 5 , 6 , 7 ]. Many examples of biologically active coumarins containing 3,4-heterocycles-fused were cited in the literature [ 2 , 3 , 8 ] including antimicrobial [ 9 , 10 , 11 , 12 ], antiviral [ 13 , 14 ], anticancer [ 15 , 16 , 17 ], antioxidant [ 18 , 19 ], and anti-inflammatory [ 20 , 21 ] activities.…”
Section: Introductionmentioning
confidence: 99%